2022
DOI: 10.1177/22785337221127133
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Review of Market-based Company Life Cycle Models

Abstract: Understanding the stages of the life cycle of companies is fundamental to their management and performance, since the characteristics of companies vary according to the moment they are going through. With this focus, the purpose of this article is to identify and analyze the models of the different company cycles found in the literature presenting comparisons with a life cycle model proposed by an author present in the industrial market. The company life cycle models were identified through a systematic litera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…In order to diagnose in which stages of the company's life cycle the intangible aspects generate impact, this research uses the model by MICHELIN et al (2022), shown in figure 2. MICHELIN et al (2022) make comparisons between several company life cycle models proposed by authors in the scientific literature and the model proposed by FISK (2009). FISK (2009) uses easy vocabulary to understand for managers present in industries.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In order to diagnose in which stages of the company's life cycle the intangible aspects generate impact, this research uses the model by MICHELIN et al (2022), shown in figure 2. MICHELIN et al (2022) make comparisons between several company life cycle models proposed by authors in the scientific literature and the model proposed by FISK (2009). FISK (2009) uses easy vocabulary to understand for managers present in industries.…”
Section: Resultsmentioning
confidence: 99%
“…FISK'S (2009) model identifies seven stages in the life cycle of companies: Create, Launch, Stabilize, Extend, Mature, Evolve and Exit. Analyzing these stages helps managers understand the company's context and is essential to overcoming challenges and seizing market opportunities (MICHELIN et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations